2005
DOI: 10.1002/cbm.4
|View full text |Cite
|
Sign up to set email alerts
|

Depression, hopelessness and suicide ideation among vulnerable prisoners

Abstract: Prisoners with a previous history of self-harm are more likely than those without to show a range of depressive symptoms than their imprisoned peers without such a history, suggesting a continued vulnerability to self-harm and perhaps suicide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
73
1
7

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(90 citation statements)
references
References 18 publications
9
73
1
7
Order By: Relevance
“…In another study, including 2,067 psychiatric outpatients, the mean total BHS score was 9.06 (SD = 5.61; Bieling, Beck, & Brown, 2000). Palmer and Connelly (2005) assessed BHS scores for prisoners with (n = 24) and without (n = 24) a history of self-harming behavior. They found that the mean BHS score for prisoners with a history of self-harming behavior was 10.13 (SD = 4.81); for offenders without a history of self-harming behavior the BHS mean score was found to be significantly lower at 6.29 (SD = 4.49).…”
Section: Beck Hopelessness Scale (Bhs)mentioning
confidence: 99%
“…In another study, including 2,067 psychiatric outpatients, the mean total BHS score was 9.06 (SD = 5.61; Bieling, Beck, & Brown, 2000). Palmer and Connelly (2005) assessed BHS scores for prisoners with (n = 24) and without (n = 24) a history of self-harming behavior. They found that the mean BHS score for prisoners with a history of self-harming behavior was 10.13 (SD = 4.81); for offenders without a history of self-harming behavior the BHS mean score was found to be significantly lower at 6.29 (SD = 4.49).…”
Section: Beck Hopelessness Scale (Bhs)mentioning
confidence: 99%
“…Where there have been studies with adolescent populations, again these have typically been with North American samples. The BDI-II (and its predecessor the Beck Depression Inventory) has been used to assess depression in offender samples (Boothby and Durham, 1999;Domalanta et al, 2003;Eidhin et al, 2002;Ivanoff et al, 1992;Palmer and Connelly, 2005). Boothby and Durham (1999) conducted a factor analysis of the BDI with incarcerated prisoner in North America, reporting four factors: cognitive symptoms, vegetative symptoms, emotional symptoms, and feelings of punishment.…”
Section: Introductionmentioning
confidence: 99%
“…Como tal, tendo em atenção que a associação entre comportamentos suicidários e perturbação psiquiátrica está particularmente documentada (Angst et al, 1999;Åsberg et al, 1995;Goss et al, 2002;He et al, 2001;Malone et al, 1995;Moreira, 2008;Palmer & Connelly, 2005) e que a ideação suicida parece ser o primeiro marcador de risco suicida (Raynolds, 1991a), este estudo tem como objectivo explorar a incidência de ideação suicida e de perturbação emocional em presos preventivos em dois momentos distintos da execução da pena, durante a primeira semana de reclusão e após seis meses de cumprimento da pena. Além disso, utilizando o ponto de corte do QIS (Raynolds, 1988), que nos permite verificar se determinado indivíduo apresenta ideação suicida, dividiu-se a amostra em dois grupos, grupo com ideação suicida (CIS) e grupo sem ideação suicida (SIS), procurando-se desta forma verificar se existem diferenças significativas ou relação de dependência entre perturbação emocional e tipo de sintomatologia psicopatológica associada (i.e., somatização, depressão, hostilidade, ansiedade, ansiedade fóbica, psicoticismo, ideação paranóide, obsessão-compulsão e sensibilidade interpessoal) mediante o grau de ideação suicida reportada em ambos os grupos.…”
unclassified